New morphological Ba0.5Sr0.5Co0.8Fe0.2O3-alpha hollow fibre membranes with high oxygen permeation fluxes - Han, D.; Tan, X.; Yan, Z.; Li, Qin; Liu, Shaomin (Elsevier Science Ltd, 2013)
Perovskite Ba0.5Sr0.5Co0.8Fe0.2O3-alpha (BSCF) hollow fibre membranes were fabricated by a combined phase inversion and sintering technique. The membranes were characterised by XRD, SEM and tested for air separation. The membrane possesses a novel morphology consisting of one dense layer and one porous layer. Oxygen permeation fluxes through the obtained hollow fibremembranes were measured in the temperature range 650–950 °C using helium sweep gas rates from 50 to 200 mL min-1. Experimental results indicated the oxygen permeation flux through the BSCF hollow fibre membrane sintered at 1050 °C was approximately 11.46 mL min-1 cm-2 at 950 °C when the helium sweep rate was kept at 200 mL min-1. The BSCF hollow fibre membrane showed a stable oxygen permeation flux of 8.60 mL min-1 cm-2 over the investigated period of 120 h at 900 °C.